Requisitos mínimos de cálculo para diseño sismo-resistente de viviendas de concreto reforzado en losas con vigas banda” - Núñez León, Carlos Rolando (2012)
The present investigation aims to determine the minimum requirements needed to calculate building "SAFE" earthquake resistant reinforced concrete slabs with beams gangs in our city; the construction of buildings is one of the cornerstones of the economy and of the most important social and financial demands. However, many families build their buildings without complying with the regulations that establish regulatory bodies to provide the security needed to live without complications in case of any eventuality that this earthquake, usually the company to save financial resources to hire staff hand unskilled labor with no knowledge of disasters that cause breach of the minimum design requirements of the Ecuadorian Code of Construction, rules and ordinances, so it did not have the necessary study of professional builders and designers become earthquake-resistant buildings vulnerable to any seismic event.